GC-MS ANALYSIS AND IN VITRO ANTIMICROBIAL ACTIVITY OF Ocotea catharinesis MEZ essential oil (LAURACEAE) - de Sousa, Danyelle Gomes; de Sousa, Yasmin Macedo; Andrade, Kelry de Souza Fechine; da Silva, Josefa Carolaine Pereira; Fernandes, Priscilla Augusta de S.; Morais-Braga, Maria Flaviana B.; do Amaral, Wanderlei; Deschamps, Cícero; Confortin, Camila; da Silva, Luiz Everson; Coutinho, Henrique Douglas Melo; Colares, Aracelio Viana (Seven Editora, 2025)
The use of plants to treat and prevent diseases is an ancestral practice of humanity. In recent years, the resistance of microorganisms to antibiotics has generated a growing interest in the research of therapeutic alternatives, including the chemical compounds present in essential oils. The aim of the present study was to evaluate the antibacterial and antifungal effect of Ocotea catharinesis essential oil (EOOc) and to identify its main compounds. The extraction of the essential oil was done by hydrodistillation for 4.5 hours, using 50g of dried leaves. To identify the chemical components, gas chromatography with mass spectrometry was used. For the microbiological tests, the strains tested included Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans and Candida tropicalis. The Minimum Inhibitory Concentration (MIC) was determined by the microdilution method. The essential oil was tested as a modulator of antibiotic resistance, using gentamicin, penicillin and norfloxacin as references for antibacterials and fluconazole for fungi, with or without the presence of the oil. Analysis of the oil revealed two main compounds: alpha pinene (13.9%) and limonene (13.4%). Alpha pinene, a terpenoid, can help reduce oxidative stress by acting as an antioxidant. The cEOOc showed resistance against E. coli and P. aeruginosa bacteria, with values equal to or greater than 1024 μg/mL, showing that gram-negative bacteria are more resistant. With the antibiotic penicillin, the EOOc showed similar results, also because of receptor proteins. Tests with Norfloxacin and Gentamicin showed values of 512 μg/mL, with no synergistic potential with antibiotics. It was observed that against the strains of Candida tropicalis, the EOOc presented a modulating effect with a lower concentration than the drug tested. The results indicate that the essential oil of Ocotea catharinesis Mez may have an antifungal effect against Candida tropicalis strains. DOI: https://doi.org/10.56238/sevened2025.018-046